2015
DOI: 10.1155/2015/314158
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Collision Tumors: An Insight into Their Origin and Clinical Significance

Abstract: Collision tumors are rare neoplasms displaying two distinct cell populations developing in juxtaposition to one another without areas of intermingling. They are rare entities with only 63 cases described in English literature. Tumors encountered are gastric adenocarcinomas colliding with lymphomas, gastrointestinal stromal tumors, squamous cell carcinomas, and neuroendocrine tumors. Their cell origin is obsolete by the time of diagnosis. Different tumorigenesis theories have been suggested to explain their beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 48 publications
(70 reference statements)
0
36
0
Order By: Relevance
“…However, several studies reported a biphasic pattern of infiltration, where both components of the CT coexisted (18-20, 54, 55). A possible explanation could be that metastasis took place before the final differentiation of the distinct histological subtypes (10). There are also cases in which each of the components metastasized to different lymph node groups (29,31).…”
Section: Pathogenesis Of Ct Is Unknown Several Theories Have Beenmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies reported a biphasic pattern of infiltration, where both components of the CT coexisted (18-20, 54, 55). A possible explanation could be that metastasis took place before the final differentiation of the distinct histological subtypes (10). There are also cases in which each of the components metastasized to different lymph node groups (29,31).…”
Section: Pathogenesis Of Ct Is Unknown Several Theories Have Beenmentioning
confidence: 99%
“…types are minimal and it is difficult to distinguish between them (1,10,11). This is why many researchers use all the above terms interchangeably.…”
mentioning
confidence: 99%
“…The cause of collision tumors such as that in our patient is unclear. Of course, coincidence is a possibility with the unfortunate meeting of two coexisting neoplasms developing independently and finally colliding [12]. This theory does not provide any particular explanation of the colliding pattern and makes no differentiation between composite and collision neoplasms [12].…”
Section: Discussionmentioning
confidence: 97%
“…In this subtype, these two distinct neoplasms develop in juxtaposition to one another, without areas of intermingling [3]. In the literature, only 26 cases of gastric adenocarcinomas colliding with lymphomas have been reported [8].…”
Section: Particularity Of Collision Tumorsmentioning
confidence: 99%